Nanotoxicology : - Monteiro-Riviere, Nancy A. (Informa Healthcare, 2007)
Nanomaterials - structures with characteristic dimensions between 1 and 100 nm -exhibit a variety of unique and tunable chemical and physical properties that have made engineered nanoparticles central components in an array of emerging technologies. The use of nanotechnology is increasing; however its potential adverse effects on human health are not well understood. In order to accurately conduct hazard assessments, scientists need to understand the broad concepts that apply to pathways of dermal, oral, and respiratory exposure. This title is designed to elucidate those concepts and to examine the interaction of nanomaterials with the biological system, including membrane transfer, screening methods, and impact on major organs.